Volar metacarpophalangeal joint dislocation. Issue 3 (1st May 2000) - Lam, W L; Fitzgerald, A M; Hooper, G
Abstract : Volar dislocation of the metacarpophalangeal joint is a very rare clinical finding. A volar dislocation of the metacarpophalangeal joint of the left index finger in a 44 year old man is reported. Closed reduction proved unsuccessful requiring subsequent open reduction and internal fixation via a combined dorsal and volar approach. The presentation, mechanism of injury and treatment of this case and other previously reported cases are discussed.